MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IXE SMP BHAKTI MULYA BATUJAJAR - Novia Putri Denati; Nelly Fitriani; Citra Megiana Pertiwi (IKIP Siliwangi, 2022)
This research is a classroom action research. The purpose of this study is to describe the application of the discovery learning model and to determine student learning outcomes after the application of the discovery learning model to mathematical problem solving abilities. The subjects of this research were 12 students of class IX E SMP Bhakti Mulya Batujajar in the academic year 2021/2022. Data collection techniques through pretest and posttest, teacher and student observation sheets, interviews and questionnaires. This research was conducted in 2 cycles with each cycle consisting of 2 meetings. Data analysis was carried out quantitatively and qualitatively. The results showed that the application of the discovery learning model went well and had an impact on increasing students' mathematical problem solving as seen from: 1) students were able to understand problems as many as 10 people (83%), 2) students were able to plan problem solving strategies as many as 9 people ( 75%), 3) students were able to do problem solving strategies as many as 10 people (83%), 4) students were able to check the correctness of the answers or the results obtained as many as 8 people (67%). Based on the description above, it is concluded that the application of the discovery learning model can improve mathematical problem solving abilities.